PENGEMBANGAN LEMBAR KEGIATAN PESERTA DIDIK BERBASIS PROBLEM BASED LEARNING (PBL) PADA MATA PELAJARAN KIMIA SMA POKOK BAHASAN LARUTAN ASAM DAN BASA - Mardasari, Desi; M. Noer, Asmadi; Rery, R. Usman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The study of Development chemistry worksheet based problem based learning on acid and base Solutions (chemistry). The result of this Development research is student worksheet product which can be used by students in the process of learning. The device development model suggested by Thiagarajan, Semmel, and Semmel (1974) is a 4-D Model consisting of 4 stages, such as: Define, Design, Develop, and Disseminate. The research development with 4-D model was conducted only Define, Design, and Development step, because the purpose of this research was limited to develop and produce a valid student worksheet to be implemented based on validator assessment. The result of research shows as the average score of the four aspect assessment of the student worksheet which is validated: content: 88,125%, language: 98,43%, presentation: 84,375%, and successive graphics: 95,31% by the validators. Thus, the overall average score of student worksheet validation the acid and base solution on Problem Based Learning is 91,56%. Based on the eligibility criteria of learning tools in Riduwan (2012), the criteria of 91,56% analysis included in valid category.Keywords : Student worksheet, Problem Based Learning, Acid and Base Solution(SchoolChemistry).